Epitaxial ferroelectric memristors integrated with silicon - Rengifo, Miguel; Aguirre, Myriam H.; Sirena, Martín; Lüders, Ulrike; Rubi, Diego (Frontiers in Nanotechnology, 2022)
Neuromorphic computing requires the development of solid-state units able to electrically mimic the behavior of biological neurons and synapses. This can be achieved by developing memristive systems based on ferroelectric oxides. In this work we fabricate and characterize high quality epitaxial BaTiO3-based memristors integrated with silicon. After proving the ferroelectric character of BaTiO3 we tested the memristive response of LaNiO3/BaTiO3/Pt microstructures and found a complex behavior which includes the co-existence of volatile and non-volatile effects, arising from the modulation of the BaTiO3/Pt Schottky interface by the direction of the polarization coupled to oxygen vacancy electromigration to/from the interface. This produces remanent resistance loops with tunable ON/OFF ratio and asymmetric resistance relaxations. These properties might be harnessed for the development of neuromorphic hardware compatible with existing silicon-based technology.